Stock Split and Rights Issue Effect on Indian Stock Market: An Empirical Study - Ray, Koustubh Kanti (Indian Journal of Finance, 2011)
Several research studies in the developed and emerging markets found that corporate events have numerous effects on the stock market. In this regard, the aim of this paper is to test the semi-strong form of efficiency in the Indian equity market following event study approach. The events considered in this paper are stock splits and rights issues that have taken place in the market from 1996 to 2008. Two events considered are tested for abnormal returns and liquidity. The data selected is free from the impact of confounding events. Minus 30 to plus 30 days investigation window is taken to test abnormal returns and to test the change in liquidity. The results suggest that the Indian market is not efficient in its semi-strong form with respect to stock split and rights issue announcements. The change in liquidity is significant for stock split at 1% significance level and found a significant change in liquidity from pre to post event period. But in case of rights issue there is no change in liquidity in both the periods.